Rethinking Religious Moderation and Anthropocentrism: Understanding Islamic Ecofeminism and Environmental Violence in The Case of the Lapindo Disaster - Nurish, Amanah; Yenigun, Halil Ibrahim; Thahir, Lukman S. (Ulumuna, 2025)
This paper investigates the Lapindo disaster in East Java that affected religious and social changes over the past two decades. Tens of thousands affected community living in the periphery of urban areas have coped with land disputes. However, religion plays an important role in fostering resilient communities. Instead of medical clinics or hospitals, new worship buildings increased in the Lapindo area. This study demonstrates that the Lapindo case is an example of environmental violence by examining critical analysis on anthropocentrism. Anthropocentrism is derived from scripture, describing humans as the most superior beings. Ecofeminism theory of Islamic perspective is critical instrument to analyze environmental violence. In addition, this research includes the concept of religious moderation that denies environmental perspectives. Given the complex issues of environmental issues in the Indonesian context, religious moderation is merely viewed as a matter of interfaith dialogue on tolerance project, yet ignoring environmental trajectory as part of religious moderation campaign. However, it has rarely been viewed as a bridge to solving social problems, such as environmental crises. The research fingding shows the rise of economic-based social crime, gender-based violence, women and children traficking, as well as poverty.